CREATIVE HUB BANJARBARU - Lesmana, Rizqy Frakhesty Islamy; Hadinata, Irwan Yudha (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The design of the creative hub in Banjarbaru was motivated by seeing the preferences oftoday's youth with creative and collaborative work. This creative hub aims to be a place that can be aplace for character building, a productive place, a place of escape that can provide benefits, a placefor gatherings to share creative ideas, develop, build relationships and so on so as to be able to give aunited effect to a group of young people. which is designed using the architectural program methodaccompanied by the concept of in motion. The program concept has two main principles, namelyexperience space, which relies on visual actors on physical properties and collaborative spaceprinciples. Conceptual methods and principles will lead to designs with a non-monotonous impressionof space and encourage actors to be creative and collaborative through spatial experience.